Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a ) \(\frac{3}{4}\)+ \(\frac{1}{6}\) = \(\frac{18}{24}\)+ \(\frac{4}{24}\)= \(\frac{22}{24}\)
b ) \(\frac{11}{12}\)- \(\frac{3}{4}\)= \(\frac{11}{12}\)- \(\frac{9}{12}\)= \(\frac{2}{12}\)
c ) \(\frac{11}{12}\)- \(\frac{1}{6}\) = \(\frac{11}{12}\)- \(\frac{2}{12}\) = \(\frac{9}{12}\)
d ) \(\frac{1}{6}\)+ \(\frac{3}{4}\)= \(\frac{4}{24}\)+ \(\frac{18}{24}\) = \(\frac{22}{24}\)
Xin lỗi mình không rút gọn nha !
a,\(\frac{14}{3}\)> \(\frac{42}{11}\)
b, 0 < \(\frac{1}{2}\)+ \(\frac{1}{3}\)+ \(\frac{1}{6}\)
c, 0 < 1 < \(\frac{1}{4}\)+ \(\frac{5}{6}\)+ \(\frac{11}{12}\)
\(\frac{3}{4}+\frac{1}{6}=\frac{9+2}{12}=\frac{11}{12}\)
\(\frac{11}{12}-\frac{3}{4}=\frac{11-9}{12}=\frac{2}{12}=\frac{1}{6}\)
\(\frac{11}{12}-\frac{1}{6}=\frac{11-2}{12}=\frac{9}{12}=\frac{3}{4}\)
\(\frac{1}{6}+\frac{3}{4}=\frac{2+9}{12}=\frac{11}{12}\)
1/3*4+1/4*5+1/5*6+...+1/11*12
=1/3-1/4+1/4-1/5+1/5-1/6+...+1/11-1/12
=1/3-1/12
=/4
nhé
\(=\frac{1}{3}-\frac{1}{4}+\frac{1}{4}-\frac{1}{5}+\frac{1}{5}-\frac{1}{6}+\frac{1}{6}-\frac{1}{7}+\frac{1}{7}-\frac{1}{8}+\frac{1}{8}-\frac{1}{9}+\frac{1}{9}-\frac{1}{10}+\frac{1}{10}-\frac{1}{11}+\frac{1}{11}-\frac{1}{12}\)
\(=\frac{1}{3}-\frac{1}{12}=\frac{1}{4}\)
1 + 2 + 3 + 4 + 5 + 6 ... + 11 + 12 + 13 = 91 nha bạn
Tick nha
\(\frac{11}{12}\) : \(\frac{1}{6}\)
= \(\frac{11}{12}\) x \(\frac{6}{1}\)
= \(\frac{66}{12}\) = \(\frac{11}{2}\)
Đáp số : \(\frac{11}{2}\)